Marine and Coastal Hazard Assessment for Three Coastal Oil Rigs - Olita, Antonio; Fazioli, Leopoldo; Tedesco, Costanza; Simeone, Simone; Cucco, Andrea; Quattrocchi, Giovanni; Ribotti, Alberto; Perilli, Angelo; Pessini, Federica; Sorgente, Roberto (Frontiers in Marine Science, 2019)
A forecasting and hazard assessment system for oil dispersion from Italian oil rigs was set up within the framework of a national research project. The system is based on 3D hydrodynamic, mesoscale resolving models providing forcing fields for a Lagrangian module of oil dispersion and slick evolution (oil transport and transformation). The tool provides,daily, the outputs of numerical simulations of possible oil spills from extraction platform sites. In this work we present the results for the 3 platforms closest to the Italian coast. Aside the operational usage, the numerical outputs are also stored and adopted to compute statistics of the slick distributions in the coastal and marine areas of interest. The hazard was assessed by means of two different indices (Hazard Index and Occurrence Index) based on the operational system outputs, for the estimation of the hazard at sea (marine hazard or aerial hazard). As short forecasts (2 days long) often do not allow the oil to reach the coast, an extra set of long-period simulations has been performed in order to compute a third Hazard Index (Coastal Hazard Index) suitable to estimate the hazard along the shorelines. The adopted methodology allowed, as a whole, to assess both coastal and marine oil spill hazard due to oil spill extraction activities. The indices constitute a basic informative layer on which the environmental risk could be also evaluated, once opportunely combined with coastal vulnerability and sensitivity layers.